2010
DOI: 10.3109/09286581003734860
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Retinopathy of Prematurity in Babol, North of Iran

Abstract: The results show that the incidence of ROP is relatively high in our region. Low GA, low BW, phototherapy, ARDS, and blood transfusion were the main risk factors for development of ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Studies conducted in developed countries suggest that infants born at ≥32 weeks’ gestation are not at risk of developing ROP 9. The percentage of any ROP in infants with BW ≤1500 g observed in our study is comparable to results from other middle-income countries such as Taiwan, Brazil and Iran, where the incidence of ROP ranged between 33% and 45% 3 13 14. The incidence of any ROP in infants with GA ≤32 weeks has been reported to be 36–50% in our country 15–18…”
Section: Discussionsupporting
confidence: 85%
“…Studies conducted in developed countries suggest that infants born at ≥32 weeks’ gestation are not at risk of developing ROP 9. The percentage of any ROP in infants with BW ≤1500 g observed in our study is comparable to results from other middle-income countries such as Taiwan, Brazil and Iran, where the incidence of ROP ranged between 33% and 45% 3 13 14. The incidence of any ROP in infants with GA ≤32 weeks has been reported to be 36–50% in our country 15–18…”
Section: Discussionsupporting
confidence: 85%
“…Our results are similar to those of an investigation carried out in Tehran (13); this may be explained by the similar facilities and relatively equal levels of prenatal care at the centers. In a recent study performed in Babol, northern of Iran, the incidence of ROP was 47.3% for infants with gestational age of ≤ 32 weeks and 33.3% for infants with birth weight of < 1500 g, whereas ROP developed in 2 infants (6%) with birth weight of > 2000 g (14). Karkhane et al found that 34.5% of premature infants had different stages of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report many systemic risk factors (respiratory distress syndrome, sepsis, necrotizing enterocolitis, intraventricular hemorrhage, and blood transfusion for neonatal severe anemia) associated with ROP [79]. The probable cause of the severity of ROP in ELBW infants could be associated with the risk factors stated above.…”
Section: Introductionmentioning
confidence: 99%